FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN MAHASISWA UIN ALAUDDIN MAKASSAR MENYELESAIKAN SKRIPSI - Sri Sulasteri; Fitriani Nur; Andi Kusumayanti (Idaarah: Jurnal Manajemen Pendidikan, 2019)
The purpose of this study was to study the factors causing delays in UIN Alauddin Makassar students in completing their thesis. This study uses a qualitative descriptive research method. The subject of this study consisted of 25 students, 5 lecturers, 5 chairpersons and department secretaries. The subject taking technique used was Purposive Sampling and Snowball Sampling techniques. Data collection techniques in the form of questionnaires, interviews, observation, and observation. Based on the results of the analysis, it is known that intelligence indicators have the highest percentage of 60%, motivation of 44%, activity of 40%, peers of 60%, supervisors of 60%, families of 52% and facilities of 64%. Based on the qualitative factors obtained 1) the factors causing student delay increase the delay in completing the study consists of two factors, namely internal factors that complement intelligence, motivation, activity, while external factors include peers, supervisors, family, and facilities.